An examination of the inadequacy of the wording of the damage claim provisions of the Oil Pollution Act of 1990, resulting in interpretative legal difficulties as revealed by claims stemming from the Deepwater Horizon Oil Spill - Bradley, Martha Magdalena (Shipping Law Unit, 2015)
Includes bibliographical references.